2016
DOI: 10.1177/0731121416683160
|View full text |Cite
|
Sign up to set email alerts
|

Attrition from Male-dominated Occupations

Abstract: Women in male-dominated occupations remain at a considerable risk of attrition. This study examines both the consequences of being an occupational minority and the effect of occupational attributes on women's exit from male-dominated occupations. Drawing on prior theories and empirical studies, I argue that women in high-status occupations are better prepared than women in low-status occupations to overcome obstacles derived from their minority status. Using the Current Population Survey data set and the Occup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
3
15
1
Order By: Relevance
“…Other studies have found that overwork in combination with motherhood make women more likely to leave male-dominated occupations (Cha, 2013), a desire for a flexible job is one of the top three reasons for women leaving the engineering field (Fouad et al, 2017) and as the proportion of men increases, women report less co-worker support and less supportive work-family culture (Cook and Minnotte, 2008;Taylor, 2010). Yet, besides the mentioned study by Cha (2013), other studies of motherhood and women's attrition find no such association (Chan, 1999;Glass et al, 2013;Torre, 2014Torre, , 2017.…”
Section: Motherhoodmentioning
confidence: 95%
See 4 more Smart Citations
“…Other studies have found that overwork in combination with motherhood make women more likely to leave male-dominated occupations (Cha, 2013), a desire for a flexible job is one of the top three reasons for women leaving the engineering field (Fouad et al, 2017) and as the proportion of men increases, women report less co-worker support and less supportive work-family culture (Cook and Minnotte, 2008;Taylor, 2010). Yet, besides the mentioned study by Cha (2013), other studies of motherhood and women's attrition find no such association (Chan, 1999;Glass et al, 2013;Torre, 2014Torre, , 2017.…”
Section: Motherhoodmentioning
confidence: 95%
“…Finally, the present study explores whether the importance of numerical minority status and motherhood for women's attrition depends on occupational class. Torre (2017) claims that research on women's attrition has overlooked the intersectionality between class and gender and that working in a male-dominated setting is not likely to have the same consequences for all women. Moreover, a central claim in the 'welfare paradox thesis' is that work-family policies of social-democratic welfare states such as Norway have different implications for women of different classes (Mandel, 2012b).…”
Section: The Role Of Occupational Classmentioning
confidence: 99%
See 3 more Smart Citations